2002
DOI: 10.1073/pnas.132051799
|View full text |Cite
|
Sign up to set email alerts
|

PRKX, a phylogenetically and functionally distinct cAMP-dependent protein kinase, activates renal epithelial cell migration and morphogenesis

Abstract: The human protein kinase X gene (PRKX) is a member of an ancient family of cAMP-dependent serine͞threonine kinases here shown to be phylogenetically distinct from the classical PKA, PKB͞Akt, PKC, SGK, and PKG gene families. Renal expression of the PRKX gene is developmentally regulated and restricted to the ureteric bud epithelium of the fetal metanephric kidney. Aberrant adult kidney expression of PRKX was found in autosomal dominant polycystic kidney disease. PRKX kinase expression markedly activated migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 48 publications
(47 reference statements)
7
71
0
Order By: Relevance
“…The current observation that ␣ v ␤ 3 disengagement is associated with the accumulation of cyclic AMP in HK-2 cells and that inhibiting cyclic AMP signaling pathway impedes HK-2 cell migration provides strong evidence for the hypothesis that cyclic AMP signaling pathway plays a role in stimulating cell mobility in response to extracellular -calpain. Previous studies have also demonstrated that cyclic AMP signaling pathway stimulates tubular epithelial cell migration in vitro (28,29). In addition, cyclic AMP signaling pathway has been implicated in the protection of these cells against the cytotoxic effect of ischemia and intracellular ATP depletion (40).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The current observation that ␣ v ␤ 3 disengagement is associated with the accumulation of cyclic AMP in HK-2 cells and that inhibiting cyclic AMP signaling pathway impedes HK-2 cell migration provides strong evidence for the hypothesis that cyclic AMP signaling pathway plays a role in stimulating cell mobility in response to extracellular -calpain. Previous studies have also demonstrated that cyclic AMP signaling pathway stimulates tubular epithelial cell migration in vitro (28,29). In addition, cyclic AMP signaling pathway has been implicated in the protection of these cells against the cytotoxic effect of ischemia and intracellular ATP depletion (40).…”
Section: Discussionmentioning
confidence: 97%
“…Unligated ␣ v ␤ 3 Integrin Induces PKA-dependent Mobility of Proximal Tubular Epithelial Cells-Integrin ligation is a potent regulator of PKA, and in turn, PKA pathway regulates actinbased migration of cells (26,27), including tubular epithelial cells (28,29). Thus, we tested the hypothesis that the cyclic AMP/PKA pathway would become activated following calpaindependent disengagement of ␣ v ␤ 3 and was involved in HK-2 cell migration.…”
Section: Extracellular -Calpain Modulates the Behavior Of Proximalmentioning
confidence: 99%
“…Pc-1 has been found to be tyrosine-phosphorylated and phosphorylated by Protein kinase A (13,14). Protein kinase X, a novel cAMP-dependent serine/ threonine kinase that regulates epithelial migration and morphogenesis is aberrantly expressed in kidney tissues from ADPKD patients (15). Mutations in Nek-family kinases Nek1 and Nek8 underlie polycystic kidney phenotypes in a pair of naturally occurring mouse models (16,17).…”
mentioning
confidence: 99%
“…Finally, some bona fide interactors may have not been present in the prey library due either to construction artifacts or to weak or absent expression in the mostly mature population of cells from which mRNA for the library was constructed. It is becoming apparent that the PrKX protein is expressed in a number of other tissue sources (Blaschke et al, 2000;Li et al, 2002), so interactions that occur with proteins specific to these tissues will be missed as well. Those caveats aside, the recovered interactors appear to lend credence to the quality of the screen.…”
Section: Discussionmentioning
confidence: 99%
“…A second interactor of PrKX was identified by a yeast two-hybrid approach as the Rep78 protein of adeno-associated virus (AAV; 12), whose interaction with PrKX reportedly modulates viral interference between AAV and adenovirus (Di Pasquale and Chiorini, 2003). More recently, PrKX was found to also play a role in neuronal differentiation (Blaschke et al, 2000) and in renal cell migration and morphogenesis (Li et al, 2002). However, to this date no innate cell substrates for the phosphorylation activity of this kinase during cell maturation have been identified.…”
Section: Introductionmentioning
confidence: 99%